Bearing retainer and corrosion-resistant bearing

By using the composite fillers of polyetherone ketones in the bearing holder, the problem of uneven diversification of the filler is solved, significantly improved the mechanical performance and wear resistance of the bearing to maintain the shelf, and meet the durability requirements of rigorous application.

CN119333477APending Publication Date: 2025-01-21NINGBO DAKE AXLETREE CO LTD

Patent Information

Application Number
CN202411528174.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, when PEEK material adds inorganic filler to the bearing cage, the filler is difficult to disperse evenly, affecting the overall performance of the composite material and unable to meet the durability requirements of strict application requirements.

Method used

By performing in-situ polymerization on the surface of the inorganic filler, a bisphenol-type compound is used to converge with 4,4'-diofluorophytzylene ketone to prepare a composite filler for polyether ethery ketone to enhance the filler and resin matrix. Compatibility and interface binding force.

Benefits of technology

Effectively improve the mechanical properties and wear resistance of polyether ether ketone, improve the overall performance of the bearing to maintain the shelf, and meet the durability requirements in the corrosive environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of bearings, and particularly discloses a bearing retainer and a corrosion-resistant bearing. The retainer is used for separating a bearing rolling body and comprises the following raw materials in parts by weight: 100 parts of polyether-ether-ketone and 10-30 parts of polyether-ether-ketone composite filler, the polyether-ether-ketone composite filler is prepared by carrying out in-situ polymerization on a bisphenol compound and 4, 4 '-difluorobenzophenone on the surface of the filler under the catalysis of an alkali metal catalyst. The ratio of the composite material can improve the mechanical strength and wear resistance of the material on the premise of ensuring the properties of self-lubrication, corrosion resistance, high temperature resistance and the like of the material, and ensures the durability of the polyether-ether-ketone retainer and a bearing rolling body in a long-term friction environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of bearings, and in particular to a bearing retainer and a corrosion-resistant bearing. Background Art

[0002] As an important part of the internal structure of the bearing, the bearing cage is mainly responsible for isolating the rolling elements, ensuring that they are evenly distributed and rolling along the track to avoid direct contact between the rolling elements, reduce wear, and improve the overall load-bearing capacity and rotation accuracy of the bearing. For working environments with strong chemical corrosion such as acids and alkalis, the cage material usually uses polyetheretherketone (PEEK) with excellent physical and chemical properties. Polyetheretherketone not only has excellent acid and alkali corrosion resistance, but also has good self-lubrication and high temperature resistance. These advantages enable the cage made of PEEK material to operate stably for a long time in harsh working environments.

[0003] In the prior art, in order to further improve the mechanical properties and wear resistance of the PEEK cage and meet more stringent application requirements, an appropriate amount of inorganic fillers, such as carbon fiber, glass fiber or graphite, are usually added to the PEEK matrix. These fillers can effectively improve the mechanical properties of the PEEK material, enhance its impact strength and wear resistance, thereby ensuring the stability and reliability of the bearing during long-term operation. However, in the actual processing process, it was found that due to the poor wettability of the PEEK material itself to the filler, it is difficult to evenly disperse the filler in the PEEK matrix, which in turn affects the overall performance of the composite material and limits the reinforcement effect of the PEEK cage.

[0004] To solve the above problems, the patent with publication number CN117024909A discloses a modified polyetheretherketone composite material, a preparation method and an application thereof, wherein the surface of the inorganic filler is modified by a silane coupling agent to promote the dispersion of the filler in the polyetheretherketone.

[0005] Although the above-mentioned silane modification methods have improved the dispersion performance of inorganic fillers in polyetheretherketone materials to a certain extent, due to compatibility issues, the silane coupling agent has very limited effect on the interface bonding between the inorganic filler and the PEEK resin, and cannot meet the durability requirements of bearing operation in a corrosive environment. Summary of the invention

[0006] The present application provides a bearing retainer and a corrosion-resistant bearing, which effectively enhance the mechanical properties and wear resistance of the polyetheretherketone retainer by improving the compatibility of the inorganic filler with the polyetheretherketone resin.

[0007] In a first aspect, the present application provides a bearing retainer for separating bearing rolling elements, wherein the raw materials thereof include, by mass: 100 parts of polyetheretherketone and 10 to 30 parts of polyetheretherketone composite filler; the polyetheretherketone composite filler is prepared by in-situ polymerization of a bisphenol compound and 4,4'-difluorobenzophenone on the surface of the filler under the catalysis of an alkali metal catalyst.

[0008] Preferably, the amount of the filler is 5 to 20% of the total mass of the bisphenol compound and 4,4'-difluorobenzophenone.

[0009] Preferably, the alkali metal catalyst is selected from one or more of potassium carbonate, sodium carbonate and cesium carbonate.

[0010] Preferably, the filler is selected from one or more of graphite, spherical alumina, spherical calcium carbonate, and glass microspheres.

[0011] The organic solvent is diphenyl sulfone or N-methylpyrrolidone; more preferably diphenyl sulfone.

[0012] Preferably, the bisphenol compound is selected from hydroquinone, 2-methylhydroquinone or resorcinol; more preferably hydroquinone.

[0013] Preferably, the melt index of the polyetheretherketone is 15 to 30 g / 10 min (380° C., 10 kg).

[0014] Preferably, the preparation method of the polyetheretherketone composite filler comprises the following steps: Prepare an alcohol aqueous solution mixed with anhydrous ethanol and deionized water, add fillers and bisphenol compounds into the alcohol aqueous solution, and disperse them ultrasonically under nitrogen protection; evaporate the alcohol aqueous solution, and dry to obtain a premix; Add the premix, 4,4'-difluorobenzophenone and the organic solvent into a reaction container, introduce nitrogen and expel the air; heat up and stir, add an alkali metal catalyst when the temperature reaches 130-160°C, heat up to 180-210°C, keep the temperature for reaction for 2-3h, then heat up to 320-330°C, keep the temperature for reaction for 1-2h, cool and grind, wash with acetone and deionized water, and dry in vacuum at 130-140°C to obtain the product.

[0015] In the present application, a polyetheretherketone-coated composite filler is obtained by in-situ polymerization of a bisphenol compound and 4,4'-difluorobenzophenone on the surface of a filler. The composite filler reduces the tendency of agglomeration between particles and is easy to be evenly dispersed in a resin matrix. In addition, the polymer on the surface of the composite filler enhances the interfacial compatibility and bonding force with the polyetheretherketone resin matrix, which helps to improve the mechanical properties of the composite material, such as bending strength and notched impact strength, and improves the wear resistance of the material.

[0016] Preferably, the molar ratio of the bisphenol compound to 4,4'-difluorobenzophenone is 1.1-1.3:1, and the surface of the polyetheretherketone composite filler is grafted with polyhydroxybenzophenone, and the grafting method is as follows: The polyetheretherketone composite filler is added to a tetrahydrofuran solvent, an organic tin catalyst is added, and diisocyanate is added dropwise under a nitrogen atmosphere. After the addition is completed, the mixture is heated and reacted for 1 to 2 hours under stirring. Then, polyhydroxybenzophenone is added, and the stirring and heating reaction are continued. After the reaction is completed, the mixture is cooled to room temperature, precipitated with anhydrous ethanol, centrifuged, washed with anhydrous ethanol, and vacuum dried to obtain a product.

[0017] Preferably, the mass ratio of the polyetheretherketone composite filler, the organic tin catalyst, the diisocyanate and the polyhydroxybenzophenone is 100:0.3-0.6:1.5-3:2-4.

[0018] Preferably, the polyhydroxybenzophenone is 2,4-dihydroxybenzophenone or 2,2',4,4'-tetrahydroxybenzophenone.

[0019] Preferably, the organotin catalyst is selected from dibutyltin dilaurate, stannous octoate or dibutyltin diacetate.

[0020] Preferably, the diisocyanate is selected from one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), and isophorone diisocyanate (IPDI).

[0021] Polyetheretherketone is a semi-crystalline material. During the injection molding process of the bearing retainer, the material will produce an uneven crystal structure. Usually, a long annealing process is used to promote the product to undergo crystal rearrangement, forming a more regular and complete crystal area, and improving the mechanical properties of the material. However, long-term high-temperature aerobic annealing will cause oxidative degradation of the molecular weight, resulting in product discoloration and decreased mechanical properties. To overcome this problem, the present application grafts polyhydroxybenzophenone on the surface of the polyetheretherketone composite filler, utilizes the antioxidant effect of polyhydroxybenzophenone, effectively captures and consumes the free radicals generated during the annealing process, inhibits the progress of oxidative degradation, and helps reduce the product's discoloration and decreased mechanical properties.

[0022] It should be noted that the premise of the polyhydroxybenzophenone grafting in the present application is that in the in-situ polymerization reaction, the molar amount of the bisphenol compound should be higher than that of 4,4'-difluorobenzophenone, and it is more appropriate to control the molar ratio to be 1.1 to 1.3:1. The polyetheretherketone obtained by polymerization at this ratio has an appropriate amount of active hydroxyl groups participating in the grafting reaction and does not affect its compatibility with the resin matrix.

[0023] Preferably, the raw material of the retainer further includes 3 to 6 parts of a flow promoter, and the flow promoter is pentaerythritol stearate and polyetherimide in a mass ratio of 1:2 to 3.

[0024] Preferably, the polyetherimide has a melt index of 50 to 80 g / 10 min (337° C., 6.6 kg).

[0025] The melt viscosity of polyetheretherketone is high and the melt fluidity is poor. After adding inorganic fillers, the fluidity decreases significantly, which is not conducive to effectively filling the mold cavity during the injection process. It may cause problems such as material shortage and voids in the parts, affecting the integrity and usability of the parts. To overcome this problem, the present application adds a flow promoter, which can improve the fluidity of the melt and ensure the integrity of the product molding. Specifically, polyetherimide can interact with the polyetheretherketone molecular chain, reduce the entanglement and internal friction between the molecular chains, and improve the melt fluidity; while pentaerythritol stearate can reduce the friction resistance between the melt and the runner, mold, and cavity, and promote the smooth and uniform flow of the melt.

[0026] Preferably, the preparation method of the bearing retainer is as follows: The polyetheretherketone, polyetheretherketone composite filler and flow promoter are mixed in proportion, added into a drying mixer, and stirred and dried at 150-180° C. to obtain a premix; The premix is ​​passed into a screw injection molding machine and injected into the mold to form the melt. The temperature of the rear part of the injection screw is about 360℃±5, the temperature of the middle part is about 365±5℃, the temperature of the front part is about 370±5℃, and the temperature of the nozzle is about 375±5℃; the mold temperature is 210±5℃; the mold is pulled onto a heat setting table, and a pressure of 0.1~0.5MPa is applied to set the mold, and the mold is cooled to room temperature to obtain a set product; Place the shaped product in an annealing furnace for annealing.

[0027] Preferably, the annealing temperature is 180-240° C., and the annealing time is 3-7 hours.

[0028] In a second aspect, the present application provides a corrosion-resistant bearing having a bearing retainer as described in any one of the above items.

[0029] Preferably, the corrosion-resistant bearing comprises a bearing inner ring, a bearing outer ring, rolling elements, a sealing ring and any one of the above-mentioned bearing retainers.

[0030] The inner ring of the above-mentioned bearing is tightly matched with the rotating shaft and is usually the part that rotates with the shaft. The outer surface of the inner ring is designed with a raceway for contacting the rolling element. The outer ring of the bearing is fixed in the bearing seat hole, and the inner surface of the outer ring is also designed with a raceway for contacting the rolling element. The rolling element can be a steel ball or a roller, which is located on the raceway between the inner ring and the outer ring, and reduces the friction between the inner ring and the outer ring by rolling. The cage is an isolation frame or retainer, and its function is to separate the rolling elements evenly, ensuring that there is enough space between them to avoid direct contact, thereby reducing wear and ensuring the smooth operation of the bearing. The cage material can be metal or plastic. The sealing ring is used in occasions that require dust and water resistance. It is installed between the inner and outer rings of the bearing to prevent external contaminants from entering the bearing and also prevent the loss of lubricating oil or grease.

[0031] The PEEK cage selected in this application has high bending strength and impact strength, can maintain stable shape under extreme working conditions, and is not easy to wear and deform. In addition, the PEEK material has good wear resistance and self-lubricating properties, which can reduce the wear between the rolling element and the cage and extend the service life of the bearing. In addition, PEEK has good resistance to a variety of chemical substances such as acids and alkalis, and can maintain good performance even in corrosive environments, which can improve the overall corrosion resistance of the bearing.

[0032] In summary, this application has the following beneficial effects: The present application obtains a polyetheretherketone coating layer by in-situ polymerization on the surface of the filler, thereby obtaining a composite filler with excellent compatibility and interfacial bonding with the polyetheretherketone resin matrix, thereby effectively improving the mechanical properties and wear resistance of the polyetheretherketone material. Furthermore, by grafting polyhydroxybenzophenone on the surface of the polyetheretherketone composite filler, the oxidative degradation phenomenon of the polyetheretherketone cage during the annealing process is effectively alleviated, ensuring the stability of the appearance and mechanical properties of the bearing cage. In addition, by adding a flow promoter composed of pentaerythritol stearate and polyetherimide, the present application can effectively improve the melt fluidity of polyetheretherketone and prevent molding problems such as material shortage and voids. DETAILED DESCRIPTION Preparation Example

[0033] Preparation Example 1: A polyetheretherketone composite filler, the preparation steps are as follows: An alcohol aqueous solution mixed with anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to water is 8:2) is prepared, 5 g of spherical calcium carbonate (D50 is 20 μm) and 0.12 mol of hydroquinone are added to the alcohol aqueous solution, and ultrasonic dispersion is performed under nitrogen protection. After 6 hours, the alcohol aqueous solution is removed by rotary evaporation, and vacuum drying is performed at 60°C to constant weight to obtain a premix.

[0034] The premix, 0.1 mol 4,4'-difluorobenzophenone and 50 mL diphenyl sulfone were added into a reaction container, and nitrogen was introduced to expel the air in the reaction container; the 4,4'-difluorobenzophenone was heated and stirred, and when the temperature reached 140°C, 0.015 mol sodium carbonate was added, and the temperature was raised to 200°C; the reaction was kept warm for 2 hours, and then the temperature was raised to 320°C, and the reaction was kept warm for 2 hours, and then cooled to room temperature, the reaction product was crushed and washed with acetone and deionized water for multiple times, and vacuum dried at 130°C for 12 hours to obtain a polyetheretherketone composite filler.

[0035] Take 10g of the above-mentioned polyetheretherketone composite filler and add it to 5L of tetrahydrofuran solvent, add 0.05g of dibutyltin dilaurate, and add 0.20g of toluene diisocyanate dropwise under a nitrogen atmosphere. After the dropwise addition is completed, heat to 70°C with stirring and react for 2h; then add 0.26g of 2,2',4,4'-tetrahydroxybenzophenone, continue to stir and heat to 85°C, and react for 5h; after the reaction is completed, cool to room temperature, precipitate with anhydrous ethanol, centrifuge the precipitate, wash with anhydrous ethanol, and vacuum dry at 80°C for 10h to obtain a polyetheretherketone composite filler grafted with polyhydroxybenzophenone.

[0036] Preparation Example 2: A polyetheretherketone composite filler, the preparation steps are as follows: An alcohol-water solution mixed with anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to water is 8:2) is prepared, 2 g of graphite (D50 is 20 μm) and 0.11 mol of hydroquinone are added to the alcohol-water solution, and ultrasonic dispersion is performed under nitrogen protection. After 6 hours, the alcohol-water solution is removed by rotary evaporation, and the solution is vacuum dried at 60°C to constant weight to obtain a premix.

[0037] The premix, 0.1 mol 4,4'-difluorobenzophenone and 50 mL diphenyl sulfone were added into a reaction container, and nitrogen was introduced to expel the air in the reaction container; the temperature was raised with stirring, and when the temperature reached 150°C, 0.01 mol sodium carbonate was added, and the temperature was raised to 180°C; the reaction was kept warm for 2 hours, and then the temperature was raised to 330°C, and the reaction was kept warm for 2 hours, and then cooled to room temperature, the reaction product was crushed and washed with acetone and deionized water for multiple times, and vacuum dried at 140°C for 10 hours to obtain a polyetheretherketone composite filler.

[0038] Take 10g of the above-mentioned polyetheretherketone composite filler and add it to 5L of tetrahydrofuran solvent, add 0.035g of dibutyltin dilaurate, and add 0.15g of toluene diisocyanate dropwise under a nitrogen atmosphere. After the dropwise addition is completed, heat to 70°C with stirring and react for 2h; then add 0.25g of 2,2',4,4'-tetrahydroxybenzophenone, continue to stir and heat to 75°C, and react for 6h; after the reaction is completed, cool to room temperature, precipitate with anhydrous ethanol, centrifuge the precipitate, wash with anhydrous ethanol, and vacuum dry at 80°C for 10h to obtain a polyetheretherketone composite filler grafted with polyhydroxybenzophenone.

[0039] Preparation Example 3: A polyetheretherketone composite filler, the preparation steps are as follows: An alcohol aqueous solution mixed with anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to water is 8:2) is prepared, 8 g of spherical calcium carbonate (D50 is 30 μm) and 0.13 mol of 2-methylhydroquinone are added to the alcohol aqueous solution, and ultrasonic dispersion is performed under nitrogen protection. After 6 hours, the alcohol aqueous solution is removed by rotary evaporation, and vacuum drying is performed at 60°C to constant weight to obtain a premix.

[0040] The premix, 0.1 mol 4,4'-difluorobenzophenone and 50 mL diphenyl sulfone were added into a reaction container, and nitrogen was introduced to expel the air in the reaction container; the temperature was raised with stirring, and when the temperature reached 140°C, 0.015 mol sodium carbonate was added, and the temperature was raised to 200°C; the reaction was kept warm for 2 hours, and then the temperature was raised to 320°C, and the reaction was kept warm for 3 hours, and the reaction was cooled to room temperature, the reaction product was crushed and washed with acetone and deionized water for multiple times, and vacuum dried at 130°C for 12 hours to obtain a polyetheretherketone composite filler.

[0041] Take 10g of the above-mentioned polyetheretherketone composite filler and add it to 5L of tetrahydrofuran solvent, add 0.055g of dibutyltin dilaurate, and add 0.3g of toluene diisocyanate dropwise under a nitrogen atmosphere. After the dropwise addition is completed, heat to 70°C with stirring and react for 2h; then add 0.4g of 2,4-dihydroxybenzophenone, continue to stir and heat to 85°C, and react for 6h; after the reaction is completed, cool to room temperature, precipitate with anhydrous ethanol, centrifuge the precipitate, wash with anhydrous ethanol, and vacuum dry at 80°C for 10h to obtain a polyetheretherketone composite filler grafted with polyhydroxybenzophenone.

[0042] Preparation Example 4, a polyetheretherketone composite filler, the preparation steps are as follows: An alcohol aqueous solution mixed with anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to water is 8:2) is prepared, 5 g of spherical calcium carbonate (D50 is 20 μm) and 0.12 mol of hydroquinone are added to the alcohol aqueous solution, and ultrasonic dispersion is performed under nitrogen protection. After 6 hours, the alcohol aqueous solution is removed by rotary evaporation, and vacuum drying is performed at 60°C to constant weight to obtain a premix.

[0043] The premix, 0.1 mol 4,4'-difluorobenzophenone and 50 mL diphenyl sulfone were added into a reaction container, and nitrogen was introduced to expel the air in the reaction container; the temperature was raised with stirring, and when the temperature reached 140°C, 0.015 mol sodium carbonate was added, and the temperature was raised to 200°C; the reaction was kept warm for 2 hours, and then the temperature was raised to 320°C, and the reaction was kept warm for 2 hours, and then cooled to room temperature, the reaction product was crushed and washed with acetone and deionized water for multiple times, and vacuum dried at 130°C for 12 hours to obtain a polyetheretherketone composite filler.

[0044] Preparation Example 5, a silane-modified filler, the preparation method is as follows: Prepare an alcohol aqueous solution mixed with anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to water is 8:2), add 100g of calcium carbonate (D50 is 20 microns) to the alcohol aqueous solution, ultrasonically disperse for 30 minutes, add 3g of vinyl triethoxysiloxane, stir and react for 20 minutes, rotary evaporate to remove the alcohol aqueous solution, and vacuum dry at 60°C to constant weight. Example

[0045] Selection of raw materials in the embodiments and comparative examples: LUVOCOM PEEK 1105-1330 is used as polyetheretherketone, and the melt index is 20 g / 10 min (380° C., 10 kg); ULTEM PEI 1040A is used as polyetherimide, and the melt index is 77 g / 10 min (337° C., 6.6 kg).

[0046] Embodiment 1, a bearing retainer is prepared according to the following steps: 10 kg of polyetheretherketone, 2.3 kg of the polyetheretherketone composite filler of Preparation Example 1, and 4.8 kg of a flow promoter were mixed in proportion, added to a drying mixer, and stirred and dried at 160° C. to obtain a premix. The flow promoter was pentaerythritol stearate and polyetherimide in a mass ratio of 1:3.

[0047] The premix is ​​introduced into the screw injection molding machine and injected into the mold to form the melt. The temperature of the rear part of the injection screw is about 360℃±5, the temperature of the middle part is about 365±5℃, the temperature of the front part is about 370±5℃, and the temperature of the nozzle is about 375±5℃; the mold temperature is 210±5℃; the mold is pulled onto the hot setting table, and a pressure of 0.2MPa is applied to set the mold, and the temperature is cooled to room temperature to obtain a set product.

[0048] The shaped product is placed in an annealing furnace for annealing at a temperature of 180-240°C for 5 hours; wherein, the first annealing temperature is 240°C, the second annealing temperature is 200°C, and the third annealing temperature is 180°C.

[0049] Embodiment 2, a bearing retainer is prepared according to the following steps: 10 kg of polyetheretherketone, 1.5 kg of the polyetheretherketone composite filler of Preparation Example 2, and 3.3 kg of a flow promoter were mixed in proportion, added to a drying mixer, and stirred and dried at 170° C. to obtain a premix. The flow promoter was pentaerythritol stearate and polyetherimide in a mass ratio of 1:2.

[0050] The premix is ​​introduced into the screw injection molding machine and injected into the mold to form the melt. The temperature of the rear part of the injection screw is about 360℃±5, the temperature of the middle part is about 365±5℃, the temperature of the front part is about 370±5℃, and the temperature of the nozzle is about 375±5℃; the mold temperature is 210±5℃; the mold is pulled onto the hot setting table, and a pressure of 0.2MPa is applied to set the mold, and the temperature is cooled to room temperature to obtain a set product.

[0051] The shaped product is placed in an annealing furnace for annealing at a temperature of 180-240°C for 5 hours; wherein, the first annealing temperature is 230°C, the second annealing temperature is 200°C, and the third annealing temperature is 180°C.

[0052] Embodiment 3, a bearing retainer is prepared according to the following steps: 10 kg of polyetheretherketone, 2.8 kg of the polyetheretherketone composite filler of Preparation Example 3, and 5.6 kg of a flow promoter were mixed in proportion, added to a drying mixer, and stirred and dried at 180° C. to obtain a premix. The flow promoter was pentaerythritol stearate and polyetherimide in a mass ratio of 1:3.

[0053] The premix is ​​introduced into the screw injection molding machine and injected into the mold to form the melt. The temperature of the rear part of the injection screw is about 360℃±5, the temperature of the middle part is about 365±5℃, the temperature of the front part is about 370±5℃, and the temperature of the nozzle is about 375±5℃; the mold temperature is 210±5℃; the mold is pulled onto the hot setting table, and a pressure of 0.2MPa is applied to set the mold, and the temperature is cooled to room temperature to obtain a set product.

[0054] The shaped product is placed in an annealing furnace for annealing at a temperature of 180-240°C for 5 hours; wherein, the first annealing temperature is 240°C, the second annealing temperature is 210°C, and the third annealing temperature is 190°C.

[0055] Example 4 is a bearing retainer, which differs from Example 1 in that the polyetheretherketone composite filler of Preparation Example 1 is replaced with an equal amount of the polyetheretherketone composite filler of Preparation Example 4.

[0056] Example 5, a bearing retainer, is different from Example 1 in that an equal amount of pentaerythritol stearate is used to replace polyetherimide in the flow promoter.

[0057] Example 6, a bearing retainer, is different from Example 1 in that pentaerythritol stearate is replaced by an equal amount of polyetherimide in the flow promoter.

[0058] Example 7, a bearing retainer, differs from Example 1 in that no flow promoter is added. Comparative Example

[0059] Comparative Example 1 is a bearing retainer, which differs from Example 7 in that the polyetheretherketone composite filler of Preparation Example 1 is replaced by an equal amount of polyetheretherketone.

[0060] Comparative Example 2 is a bearing retainer, which differs from Example 7 in that the polyetheretherketone composite filler of Preparation Example 1 is replaced by an equal amount of the silane-modified filler of Preparation Example 5. Performance testing

[0061] Test 1: Mechanical properties test Bending strength: According to ISO 178 standard, the bending strength of the material is tested by a universal testing machine. The specimen is cut from the bearing cage and has a size of 80 mm × 9 mm × 4 mm.

[0062] Notched impact strength (23°C): Tested in accordance with ISO 180 / A, with the specimen being type A.

[0063] Test 2: Wear resistance test The dry friction test is used to judge the wear amount and corresponding friction coefficient of the bearing retainer sample. The dry friction test is tested by the end face friction and wear tester. The test conditions are: constant speed and load, linear speed 0.4m / s, load 12MPa, test duration 60min; the friction coefficient is automatically obtained by the end face friction and wear tester program. The wear amount is characterized by the depth of the wear mark. After the dry friction test, the sample is placed on the profilometer for measurement. The four sides of the sample are selected for measurement, and the results are averaged. Before the test, the surface of the sample needs to be cleaned with a cotton ball with acetone.

[0064] Test 3: Yield test The finished bearing retainers obtained in the embodiment and the comparative example were observed, and the finished products with poor appearance such as missing material and voids were recorded as defective products, and the yield rate of each component product was obtained by statistics.

[0065] Table 1. Test results

[0066] Combining Examples 1 to 7 and Comparative Examples 1 to 2 and Table 1, it can be seen that the filler grafted on the surface of polyetheretherketone by in-situ polymerization in the present application has superior mechanical strength and wear resistance to the filler without grafting modification or grafting modification with a silane coupling agent. The reason may be that the filler grafted and coated with polyetheretherketone on the surface has a more prominent ability to improve the compatibility of the filler with the resin matrix and enhance the interfacial bonding force.

[0067] It can be seen from Example 1 and Example 4 and Table 1 that grafting polyhydroxybenzophenone on the surface of the polyetheretherketone composite filler is beneficial to improving the mechanical strength and wear resistance of the resulting composite material. The reason may be that polyhydroxybenzophenone can capture free radicals generated during long-term annealing, inhibit the oxidative degradation of the polyetheretherketone molecular chain, and reduce strength loss.

[0068] Combining Example 1 and Examples 5 to 7 with Table 1, it can be seen that adding a flow promoter compounded with pentaerythritol stearate and polyetherimide to the polyetheretherketone resin helps to improve the yield rate. The reason may be that the flow promoter can improve the melt fluidity and reduce defects caused by fluidity such as lack of material and voids during injection molding.

[0069] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A bearing retainer, characterized in that: Used for separating bearing rolling elements, the raw materials include, by mass, 100 parts of polyetheretherketone and 10-30 parts of polyetheretherketone composite filler; the polyetheretherketone composite filler is prepared by in-situ polymerization of bisphenol compounds and 4,4'-difluorobenzophenone on the filler surface under the catalysis of an alkali metal catalyst.

2. The bearing retainer according to claim 1, characterized in that: The amount of the filler is 5-20% of the total mass of the bisphenol compound and 4,4'-difluorobenzophenone.

3. The bearing retainer according to claim 1, characterized in that: The filler is selected from one or more of graphite, spherical alumina, spherical calcium carbonate and glass microspheres.

4. The bearing retainer according to claim 1, characterized in that: The alkali metal catalyst is selected from one or more of potassium carbonate, sodium carbonate and cesium carbonate; the organic solvent is diphenyl sulfone or N-methylpyrrolidone.

5. The bearing retainer according to claim 1, characterized in that: The preparation method of the polyetheretherketone composite filler comprises the following steps: Prepare an alcohol aqueous solution mixed with anhydrous ethanol and deionized water, add fillers and bisphenol compounds into the alcohol aqueous solution, and disperse them ultrasonically under nitrogen protection; evaporate the alcohol aqueous solution, and dry to obtain a premix; Add the premix, 4,4'-difluorobenzophenone and the organic solvent into a reaction container, introduce nitrogen and expel the air; heat up and stir, add an alkali metal catalyst when the temperature reaches 130-160°C, heat up to 180-210°C, keep the temperature for reaction for 2-3h, then heat up to 320-330°C, keep the temperature for reaction for 1-2h, cool and grind, wash with acetone and deionized water, and dry in vacuum at 130-140°C to obtain the product.

6. The bearing retainer according to claim 5, characterized in that: The molar ratio of the bisphenol compound to 4,4'-difluorobenzophenone is 1.1-1.3:1, and polyhydroxybenzophenone is grafted on the surface of the polyetheretherketone composite filler, and the grafting method is as follows: The polyetheretherketone composite filler is added to a tetrahydrofuran solvent, an organic tin catalyst is added, and diisocyanate is added dropwise under a nitrogen atmosphere. After the addition is completed, the mixture is heated and reacted for 1 to 2 hours under stirring. Then, polyhydroxybenzophenone is added, and the stirring and heating reaction are continued. After the reaction is completed, the mixture is cooled to room temperature, precipitated with anhydrous ethanol, centrifuged, washed with anhydrous ethanol, and vacuum dried to obtain a product.

7. The bearing retainer according to claim 6, characterized in that: The mass ratio of the polyetheretherketone composite filler, the organic tin catalyst, the diisocyanate and the polyhydroxybenzophenone is 100:0.3-0.6:1.5-3:2-4.

8. The bearing retainer according to claim 6, characterized in that: The polyhydroxybenzophenone is 2,4-dihydroxybenzophenone or 2,2',4,4'-tetrahydroxybenzophenone.

9. The bearing retainer according to claim 1, characterized in that: The raw materials of the retainer also include 3 to 6 parts of a flow promoter, and the flow promoter is pentaerythritol stearate and polyetherimide in a mass ratio of 1:2 to 3.

10. A corrosion-resistant bearing, characterized in that: The corrosion-resistant bearing comprises a bearing inner ring, a bearing outer ring, rolling elements, a sealing ring and the bearing retainer according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Modified polyether-ether-ketone composite material, preparation method and application

    CN117024909A

Cited By

  • Super-corrosion-resistant titanium alloy wire and preparation method thereof

    CN120904766A